2016
DOI: 10.1371/journal.pgen.1006203
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Expression of the piRNA-Resistant Masculinizer Gene Induces Female-Specific Lethality and Partial Female-to-Male Sex Reversal in the Silkworm, Bombyx mori

Abstract: In Bombyx mori (B. mori), Fem piRNA originates from the W chromosome and is responsible for femaleness. The Fem piRNA-PIWI complex targets and cleaves mRNAs transcribed from the Masc gene. Masc encodes a novel CCCH type zinc-finger protein and is required for male-specific splicing of B. mori doublesex (Bmdsx) transcripts. In the present study, several silkworm strains carrying a transgene, which encodes a Fem piRNA-resistant Masc mRNA (Masc-R), were generated. Forced expression of the Masc-R transgene caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(75 citation statements)
references
References 61 publications
7
68
0
Order By: Relevance
“…While alternative genomic integration sites and the utilization of a splicing cassette based on the DBM dsx gene described here may reduce these fitness costs, a degree of transgene-based fitness reduction in males may be unavoidable as the default lepidopteran splicing pattern of dsx in both sexes is the female splicing isoform (Kiuchi et al, 2014;Fukui et al, 2015;Lee et al, 2015), so the expression profile of tTAV in such designs is probably not sex-specific in very early embryos. In B. mori, transgenic expression of a Fem-resistant Masc transcript led to both female-specific lethality and partial female-to-male sex reversal (Sakai et al, 2016). Although it remains to be determined whether a similar piRNA-based system operates in DBM, one might speculate that expression of an analogous, nucleotide recoded, PxyMasc transcript in DBM females would act as a dominant female-specific lethal effector for an fsRIDL systemprobably with fewer fitness costs to transgenic males as this is an endogenously expressed gene in this sex.…”
Section: Discussionmentioning
confidence: 99%
“…While alternative genomic integration sites and the utilization of a splicing cassette based on the DBM dsx gene described here may reduce these fitness costs, a degree of transgene-based fitness reduction in males may be unavoidable as the default lepidopteran splicing pattern of dsx in both sexes is the female splicing isoform (Kiuchi et al, 2014;Fukui et al, 2015;Lee et al, 2015), so the expression profile of tTAV in such designs is probably not sex-specific in very early embryos. In B. mori, transgenic expression of a Fem-resistant Masc transcript led to both female-specific lethality and partial female-to-male sex reversal (Sakai et al, 2016). Although it remains to be determined whether a similar piRNA-based system operates in DBM, one might speculate that expression of an analogous, nucleotide recoded, PxyMasc transcript in DBM females would act as a dominant female-specific lethal effector for an fsRIDL systemprobably with fewer fitness costs to transgenic males as this is an endogenously expressed gene in this sex.…”
Section: Discussionmentioning
confidence: 99%
“…The fem piRNA-PIWI complex recognizes and cleaves Masculinizer (Masc) messenger RNA (mRNA), which is transcribed from a gene located on the Z chromosome. Masc controls sex-specific splicing of doublesex (dsx) and the expression of IGF-II mRNA-binding protein (Imp) (Sakai et al, 2016). Masc has been well characterized in B. mori Sakai et al, 2016), and the Masc gene has been reported to control the sex-determination cascade in lepidopteran pest Trilocha varians (Lee et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Masc controls sex-specific splicing of doublesex (dsx) and the expression of IGF-II mRNA-binding protein (Imp) (Sakai et al, 2016). Masc has been well characterized in B. mori Sakai et al, 2016), and the Masc gene has been reported to control the sex-determination cascade in lepidopteran pest Trilocha varians (Lee et al, 2015). Recently, it was shown that the bacterium Wolbachia targets the host Masc gene to accomplish male-killing in the pest Ostrinia, also a lepidopteran species (Fukui et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…BmMasc is located on the Z chromosome and is a target gene of Fem‐derived Piwi‐interacting RNA, which controls both dosage compensation and masculinization (Kiuchi et al ., ). Ectopic expression of BmMasc demonstrated that BmMasc induces maleness at the morphological level and is sufficient for spermatogenesis (Sakai et al ., ). Knockout of BmMasc results in males with degenerative testes and defective external genitals (Xu et al ., ).…”
Section: Introductionmentioning
confidence: 97%